Winter swells over Bombay High area - MUKHERJEE, A. K.; NARASIMHAM, A. L.; SIVARAMAKRISHNAN, T. R. (MAUSAM, 1977)
The swells over Bombay High area during the winter months are investigated here. Changes in swell heights do occur in winter. Apart from the seasonal high pattern and the passage of western disturbances, the seasonal easterly trough of west coast is also found to be intimately connected in causing the changes in swell parameters.